Successful treatment with baloxavir marboxil of a patient with peramivir-resistant influenza A/H3N2 with a dual E119D/R292K substitution after allogeneic hematopoietic cell transplantation: a case report - Harada, Naonori; Shibata, Wataru; Koh, Hideo; Takashita, Emi; Fujisaki, Seiichiro; Okamura, Hiroshi; Nanno, Satoru; Yamada, Koichi; Nakamae, Hirohisa; Hino, Masayuki; Kakeya, Hiroshi (BMC infectious diseases, 2020)
Extended use of oseltamivir in an immunocompromised host could reportedly induce neuraminidase gene mutation possibly leading to oseltamivir-resistant influenza A/H3N2 virus. To our knowledge, no report is available on the clinical course of a severely immunocompromised patient with a dual E119D/R292K neuraminidase mutated-influenza A/H3N2 during the administration of peramivir. In a highly immunocompromised host, clinicians should take care when peramivir is used for extended periods to treat influenza virus A/H3N2 infection as this could potentially leading to a dual E119D/R292K substitution in neuraminidase protein. Baloxavir marboxil may be one of the agents that can be used to treat this type of mutated influenza virus infection.